Pemberdayaan Aparatur Sipil Negara dalam Meningkatkan Kinerja Pegawai di Sekretariat Daerah Kabupaten Katingan (Implementasi UU No.5 Tahun 2014 tentang ASN) - Indah Tri Handayani; Irwani Irwani; Farid Zaky Yopiannor; Suffianor Suffianor (Anterior Jurnal, 2018)
Empowerment is a process to create the strength or ability of a person or some people. Taking into account this phenomenon, the empowerment of the apparatus is a strategic choice to increase the capacity and competence of the apparatus to support the performance of employees in the Katingan Regency Regional Secretariat. The author uses descriptive research with qualitative analysis methods. The results of the study on Empowerment through Education and training both in the Administrative, Technical and Leadership Fields have brought better changes, namely, not only the increased ability of the apparatus but also can improve the attitudes and behavior of the apparatus to improve performance. This is indicated by the increase in apparatuses which have training legality, both in the field of general administration, technical areas and in the field of leadership. Education provided is undoubtedly essential for employees to improve their performance so that with this education and training employees can work professionally. Empowerment carried out through employee mutations has reduced employee saturation in carrying out their duties and at the same time provides new experiences and increases employee competence in carrying out their duties. Empowerment carried out through the granting of authority and responsibility turns out to encourage employee motivation to improve performance, because in giving power is based on rationality consideration so that it can foster employee motivation to be more responsible for delegated work